Pengaruh Literasi Keuangan, Finansial Teknologi, Dan Sikap Keuangan Terhadap Minat Belanja Di E-Commerce : (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya Pengguna Aplikasi Shopee) - Della Millenia Sari; Ery Teguh Prasetyo; Dody Kurniawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to examine the influence of financial literacy, financial technology and financial attitudes on shopping interest in e-commerce (case study of students at the Faculty of Ereconomy and Business, Bhayangkara University, Greater Jakarta, users of the Shopee application). Quantitative Research Method and for the sample in this study the author used a purposive sampling method. The sample size used in this research was 96 respondents and focused on Shopee users who were also students at the Faculty of Economics and Business, Bhayangkara University, Greater Jakarta. The analysis method uses the Multiple Linear Regression method and the research scale uses a Likert scale. The results of this research show that partially the Financial Literacy variable (X1) has a positive and significant effect on Shopping (Y) of 3.787 > 1.986 with a significant value (0.000 < 0.05), the Financial Technology variable (X2) has a positive and significant effect on Shopping Interest (Y) is 2.610 > 1.986 with a significant value of (0.011 < 0.05), the Financial Attitude variable (X1) has a positive and significant effect on Shopping (Y) of 5.097 > 1.986 with a significant value of (0.000 < 0.05). Then simultaneously there is a positive and significant influence on Shopping Interest with a result of 33,670 > 2.70 with a significant value of 0.000 < 0.05.